Synthesis and Anticoccidial Activities of Quinoline Carboxylate Derivatives with Methyl (E)-2-(3-methoxy)acrylate Moiety - Liu, Yuan; Weng, Ya-Biao; Chen, Zhao-Bing; Wang, Yu-Liang (Asian Journal of Chemistry, 2013)
A series of novel quinoline carboxylate derivatives with methyl (E)-2-(3-methoxy) acrylate group were designed and synthesized as anticoccidial medicines. The structures were confirmed by 1H NMR, IR and HR-MS spectra. The biological activities were primarily evaluated according to the anticoccidial index method. The results indicated that these compounds (7c, 7d, 7e, 7g) exhibited anticoccidial activities against Eimeria tenella. In particular, the anticoccidial index of 6-decyloxy-7-ethoxy-4-6-[2-(2-methoxy-1-methoxycarbonyl-vinyl)phenoxy]pyrimidin-4-yloxy-quinoline-3-carboxylic acid ethyl ester (7e) was 168.7, which indicated that the compound has a good anticoccidial activity.